2000
DOI: 10.1038/75977
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SPINK5, encoding a serine protease inhibitor, cause Netherton syndrome

Abstract: We describe here eleven different mutations in SPINK5, encoding the serine protease inhibitor LEKTI, in 13 families with Netherton syndrome (NS, MIM256500). Most of these mutations predict premature termination codons. These results disclose a critical role of SPINK5 in epidermal barrier function and immunity, and suggest a new pathway for high serum IgE levels and atopic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
580
1
18

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 777 publications
(618 citation statements)
references
References 14 publications
9
580
1
18
Order By: Relevance
“…Peeling skin disease (Fig 4, D) 124 has to be differentiated from NS. Unlike NS, peeling skin disease does not show hair anomalies, is not caused by SPINK5 mutations, 125 and has different immunochemical features, 126 but may also be accompanied by atopic diathesis. 3,124 Diseases related to inherited ichthyoses A certain number of MEDOC forms can be regarded as phenotypically and/or etiologically related to ichthyosis, or have to be considered as differential diagnoses.…”
Section: Other Diseases Considered In the Classification Of Inheritedmentioning
confidence: 99%
“…Peeling skin disease (Fig 4, D) 124 has to be differentiated from NS. Unlike NS, peeling skin disease does not show hair anomalies, is not caused by SPINK5 mutations, 125 and has different immunochemical features, 126 but may also be accompanied by atopic diathesis. 3,124 Diseases related to inherited ichthyoses A certain number of MEDOC forms can be regarded as phenotypically and/or etiologically related to ichthyosis, or have to be considered as differential diagnoses.…”
Section: Other Diseases Considered In the Classification Of Inheritedmentioning
confidence: 99%
“…5 Eighty percent of patients with AD cases show elevated total serum IgE levels, 6 and atopic mechanisms dominate our current understanding of the pathogenesis of AD. 7 Serine protease inhibitor Kazal-type 5 (SPINK5) is responsible for Netherton syndrome, 8 a rare recessive skin disorder that is accompanied by atopy. 9 The SPINK5 gene comprises 33 exons and spans approximately 61 kb on human chromosome 5q32.…”
mentioning
confidence: 99%
“…8 SPINK5 is expressed in thymus, tonsil and oral mucosa, 10 and it is suggested that abnormal maturation of T lymphocytes in patients with Netherton syndrome alters Th2-type responsiveness to allergens, leading to elevated IgE levels. 8 A recent study of Caucasian AD families showed that maternally derived alleles of the SPINK5 gene are associated with development of atopic diseases such as AD and asthma, suggesting a parent-oforigin effect in the development of atopic diseases. 11 To confirm an involvement of the SPINK5 gene in atopic diseases, these findings must be replicated in an independent set of families.…”
mentioning
confidence: 99%
“…Collec tively, these detriments represent a serious chal lenge to neonate health and promote frequent complications, including hypernatremic dehy dration, failure to thrive and recurrent bacterial infections that can be life threatening. Previ ously, we established that the defective gene in NS is SPINK5 (Chavanas et al, 2000), which encodes the multidomain protease inhibitor, lymphoepithelial Kazal type inhibitor (LEKTI). To date, the majority of SPINK5 mutations known to cause NS introduce a premature stop codon and result in a lack of detectable LEKTI expression (Hovnanian, 2013).…”
mentioning
confidence: 99%